Sirtuin1 Targeting Reverses Innate and Adaptive Immune Tolerance in Septic Mice - Ayana N. Martin; Martha Alexander-Miller; Barbara K. Yoza; Vidula Vachharajani; Charles E. McCall (Journal of Immunology Research)
Resistance and tolerance to infection are two universal fitness and survival strategies used by inflammation and immunity in organisms and cells to guard homeostasis. During sepsis, however, both strategies fail, and animal and human victims often die from combined innate and adaptive immune suppression with persistent bacterial and viral infections. NAD+-sensing nuclear sirtuin1 (SIRT1) epigenetically guards immune and metabolic homeostasis during sepsis. Pharmacologically inhibiting SIRT1 deacetylase activity in septic mice reverses monocyte immune tolerance, clears infection, rebalances glycolysis and glucose oxidation, resolves organ dysfunction, and prevents most septic deaths. Whether SIRT1 inhibition during sepsis treatment concomitantly reverses innate and T cell antigen-specific immune tolerance is unknown. Here, we show that treating septic mice with a SIRT1 selective inhibitor concordantly reverses immune tolerance splenic dendritic and antigen-specific tolerance of splenic CD4+ and CD8+ T cells. SIRT1 inhibition also increases the ratio of IL12 p40+ and TNFα proinflammatory/immune to IL10 and TGFβ anti-inflammatory/immune cytokines and decreases the ratio of CD4+ TReg repressor to CD4+ activator T cells. These findings support the unifying concept that nuclear NAD+ sensor SIRT1 broadly coordinates innate and adaptive immune reprogramming during sepsis and is a druggable immunometabolic enhancement target.